Gender Equality in Chile Towards a Better Sharing of Paid and Unpaid Work (OECD Publishing, 2021)
The OECD review of Gender Equality in Chile: Towards a Better Sharing of Paid and Unpaid Work is the first of a series addressing Latin American and the Caribbean countries. It compares gender gaps in labour and educational outcomes in Chile with other countries. Particular attention is put on the uneven distribution of unpaid work, and the extra burden this places on women. It investigates how policies and programmes in Chile can make this distribution more equitable. The first part of the report reviews the evidence on gender gaps and on what causes these, including the role played by attitudes. The second part develops a comprehensive framework to address these challenges, presenting a broad range of options to reduce the unpaid work burden falling on women, and to increase women's labour income. The final part discusses the impact of the COVID-19 crisis and considers how the policy priorities of the government will have to change to address these